2010
DOI: 10.1136/jmg.2010.079962
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer susceptibility loci on chromosome 8q23.3 and 11q23.1 as modifiers for disease expression in lynch syndrome

Abstract: The authors were able to replicate the association between the CRC susceptibility loci on chromosomes 8q23.3 and 11q23 and the risk of developing CRC in patients with Lynch syndrome, but the association could only be detected in MLH1 mutation carriers in this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
35
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 24 publications
1
35
0
Order By: Relevance
“…12 These results were partly confirmed in a cohort of Australian and Polish MMR mutation carriers, but were not replicated in a French cohort. 13,14 We selected the hTERT variant rs2075786 by somehow combining candidate gene and GWAS-based approaches. First, hTERT has an important role at very early stages of carcinogenesis, its expression has been linked to increased susceptibility to tumorigenesis, and rs2075786 has been associated with cancer risk.…”
Section: Rs2075786 and Telomere Lengthmentioning
confidence: 99%
See 1 more Smart Citation
“…12 These results were partly confirmed in a cohort of Australian and Polish MMR mutation carriers, but were not replicated in a French cohort. 13,14 We selected the hTERT variant rs2075786 by somehow combining candidate gene and GWAS-based approaches. First, hTERT has an important role at very early stages of carcinogenesis, its expression has been linked to increased susceptibility to tumorigenesis, and rs2075786 has been associated with cancer risk.…”
Section: Rs2075786 and Telomere Lengthmentioning
confidence: 99%
“…11 In contrast, two genetic variants previously identified in CRC genome-wide association studies (GWAS), rs16892766 and rs3802842, might modify cancer risk in LS families. [12][13][14] Telomeres are located at the end of chromosomes and protect the chromosome ends from nucleolitic degradation, end-to-end fusions and irregular recombination, being thus critical for genome stability and integrity. Telomeres progressively shorten with each cell replication cycle.…”
Section: Introductionmentioning
confidence: 99%
“…[38][39][40] Thus, variants on 8q23.3 and 11q23.1 have been found to modify colorectal cancer risk in Lynch syndrome. 41,42 On the other hand, some polygenic diseases such as age-related macular degeneration have been attributed to several genetic variants with considerably large effect sizes (eg, the variants in CFH; odds ratio ¼ 4.6), which taken together, account for 50% of the heritability of the disease. By contrast, 32 genetic variants identified as being associated with Crohn's disease are able to explain only 20% of the heritability.…”
Section: Common Approaches To Interrogate the Genetic Basis Of Diseasementioning
confidence: 99%
“…1,2 If these SNPs also predicted CRC risk for carriers of mismatch repair (MMR) gene mutations (which cause Lynch syndrome), there is potential to use them for a personalized risk assessment and therefore a tailored surveillance program. Two studies 3,4 have reported that MMR gene mutation carriers, who also carry either the C-allele of rs16892766 on 8q23.3 or the C-allele of rs3802842 on 11q23.1, are at increased risk of CRC compared with carriers without these alleles, especially for MLH1 mutation carriers 4 and especially for females. 3 However, another study 5 of these SNPs observed no such association.…”
mentioning
confidence: 99%
“…In a recent study, Talseth-Palmer et al 6 conducted a pooled analysis by combing the studies by Wijnen et al 3 and Talseth-Palmer et al 4 to investigate the role of seven SNPs from six independent loci on CRC risk for MMR gene mutation carriers. They reported that carriers of the C-allele of rs16892766 (8q23.3) and the C-allele of rs3802842 (11q23.1) are at increased risk of CRC for MLH1 mutation carriers.…”
mentioning
confidence: 99%